2014
DOI: 10.1080/10408398.2012.708909
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds of Cereals and Their Antioxidant Capacity

Abstract: Phenolic compounds play an important role in health benefits because of their highly antioxidant capacity. In this review, total phenolic contents (TPCs), phenolic acid profile and antioxidant capacity of the extracted from wheat, corn, rice, barley, sorghum, rye, oat, and millet, which have been recently reported, are summarized. The review shows clearly that cereals contain a number of phytochemicals including phenolics, flavonoids, anthocyanins, etc. The phytochemicals of cereals significantly exhibit antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
171
1
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(189 citation statements)
references
References 72 publications
7
171
1
10
Order By: Relevance
“…Previous in vitro studies have shown that the antioxidant activity of fruits, vegetables and cereals was positively correlated with phenolic content (Sánchez‐Salcedo et al ., ; Lingua et al ., ; Van Hung, ). The lotus leaf is a rich source of phenolic compounds including many flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies have shown that the antioxidant activity of fruits, vegetables and cereals was positively correlated with phenolic content (Sánchez‐Salcedo et al ., ; Lingua et al ., ; Van Hung, ). The lotus leaf is a rich source of phenolic compounds including many flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…They are abundantly present in foods such as berries [1], nuts [2], coffee and tea [3] and whole grains [4]. Importantly, a recent meta-analysis showed that phenolic acid-rich foods decrease the risk of depression [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Bran is the outer layer protecting the grain, and germ is the kernel's reproduction system. Whereas wheat endosperm contains mostly starch and protein, bran and germ are rich in dietary fibre, vitamins, minerals and phytochemicals playing an important role in nutrition and health benefits for humans [2]. The customers are, therefore, strongly recommended to consume whole grain foods with at least three servings per day.…”
Section: Introductionmentioning
confidence: 99%